Memahami Metode Kualitatif - Somantri, Gumilar Rusliwa (Makara Human Behavior Studies in Asia, 2005)
Qualitative method has been widely be adopted in research practices in Indonesian tradition of social sciences including sociology. However, it seems there is misunderstanding on the method that is seen as additional to the quantitative one. This literature study intend to discuss related issues to the strengths and weaknesses of qualitative method. We do conclude here, that the method has productive potential for fostering the develomment of social theories as well as methodology in the context of Indonesian world. Hence, it is possible to bring Indonesian social sciences especially sociology into equal position of future dialog with the counterparts from the Western communities.